Chemokine receptor expression by inflammatory T cells in EAE - Mony, Jyothi Thyagabhavan; Khorooshi, Reza; Owens, Trevor (Frontiers in Cellular Neuroscience, 2014)
Chemokines direct cellular infiltration to tissues, and their receptors and signaling pathways represent targets for therapy in diseases such as multiple sclerosis (MS). The chemokine CCL20 is expressed in choroid plexus, a site of entry of T cells to the central nervous system (CNS). The CCL20 receptor CCR6 has been reported to be selectively expressed by CD4+ T cells that produce the cytokine IL-17 (Th17 cells). Th17 cells and interferon-gamma (IFNγ)-producing Th1 cells are implicated in induction of MS and its animal model experimental autoimmune encephalomyelitis (EAE). We have assessed whether CCR6 identifies specific inflammatory T cell subsets in EAE. Our approach was to induce EAE, and then examine chemokine receptor expression by cytokine-producing T cells sorted from CNS at peak disease. About 7% of CNS-infiltrating CD4+ T cells produced IFNγ in flow cytometric cytokine assays, whereas less than 1% produced IL-17. About 7.7% of CD4+ T cells produced both cytokines. CCR6 was expressed by Th1, Th1+17 and by Th17 cells, but not by CD8+ T cells. CD8+ T cells expressed CXCR3, which was also expressed by CD4+ T cells, with no correlation to cytokine profile. Messenger RNA for IFNγ, IL-17A, and the Th1 and Th17-associated transcription factors T-bet and RORγt was detected in both CCR6+ and CXCR3+ CD4+ T cells. IFNγ, but not IL-17A mRNA expression was detected in CD8+ T cells in CNS. CCR6 and CD4 were co-localized in spinal cord infiltrates by double immunofluorescence. Consistent with flow cytometry data some but not all CD4+ T cells expressed CCR6 within infiltrates. CD4-negative CCR6+ cells included macrophage/microglial cells. Thus we have for the first time directly studied CD4+ and CD8+ T cells in the CNS of mice with peak EAE, and determined IFNγ and IL17 expression by cells expressing CCR6 and CXCR3. We show that neither CCR6 or CXCR3 align with CD4 T cell subsets, and Th1 or mixed Th1+17 predominate in EAE.